Viewpoint: For the Love of Complexity: Educating Beyond Enthusiasms - Forsthefel, Thomas (Journal of Hindu-Christian studies, 2015)
I'D like to begin this essay by sharing a brief personal narrative which I trust is illustrative. I was raised in the Roman Catholic tradition, but like many students in college ignored or rejected much of it in favor of other worlds of meaning and value. However, late in my undergraduate career, at Georgetown, I found myself in net of emotional and spiritual distress and felt existentially unmoored. That distress was the antecedent and catalyst for a profound re-encounter with the heart of Christian faith, a conversion or, perhaps better, re-conversion, as my faith certainly was meaningful to me as a young boy growing up in a traditional Catholic household. Nevertheless, this later breakthrough was stimulated by an old-fashioned encounter at a Southern Baptist church, replete with altar calls, witnessing, and confessing with one's lips that Jesus is Lord to attain certain salvation.